The System of Tactical Tasks and Means of Their Solution in Various Situations of Investigation of Illegal Cultivation of Plants Containing Drugs or Psychotropic Substances or Their Precursors - E. E. Kosmodemyanskaya; M. G. Ermakov (Сибирское юридическое обозрение, 2018)
This article deals with the problem of counteracting illicit cultivation of narcotic plants, which is a fairly common crime in the sphere of drug trafficking. The idea that counteraction to these crimes is possible with the help of modern methods of investigation is substantiated. The authors of the article consider such structural elements of the methodology for investigating the illicit cultivation of plants containing narcotic drugs or psychotropic substances or their precursors, as initial investigative situations and a system of tactical tasks in each of them. The authors focus on the need to determine the sequence of actions, to make out an algorithm of the investigation process in order to improve the quality of the preliminary investigation. Based on the study, the authors proposed a set of general and facultative tactical problems of investigation of this type of crimes, subject to resolution, the variability of which is determined by the initial investigative situation. The study justifies the idea of the need to improve the existing forensic methods and the development of universal guidelines, the construction of an investigator's algorithm for investigating crimes of this type.